The Effectiveness of Therapeutic Approaches for Narcissistic Personality Disorder in Adolescents - Konto Iskandar Dinata; Umi Nur Kholifah; Fitri Ramadhani (Psikologi Prima, 2025)
This study aims to evaluate the effectiveness of various therapeutic methods in overcoming Narcissistic Personality Disorder (NPD) based on study results from Indonesian scientific journals in the last five years. The method used was a literature review of five selected articles that discussed therapeutic interventions such as Rational Emotive Behavior Therapy (REBT), self-control techniques, and the Gestalt approach. The review showed that all three approaches are effective in reducing narcissistic symptoms, especially in adolescents and young adults. REBT and self-control techniques proved capable of changing dysfunctional thought patterns, while group counseling with the Gestalt approach contributed to increasing self-awareness and personal responsibility. Although the findings are promising, there are limitations such as methodological variations and the age range of the subjects that pose challenges in applying the results generally. This study contributes to the development of counseling practices in Indonesia and encourages further research with more diverse designs and populations.